Community empowerment through the practice of balanced nutrition diets for mothers of infants and toddlers in Mandangin Island, Sampang Regency, 3rd year - Widati Fatmaningrum; Djohar Nuswantoro; Atika Atika; Patmawati Patmawati (Future Science, 2018)
Community participation related to nutritional problems on Mandangin Island is caused by a lack of public appreciation of health because they think that if their babies / infants are fully immunized, they don't need to be weighed again like they were when they were babies. Busy mothers as housewives also affect the low participation of the community, so the nutritional problem in Mandangin is still a priority for health care. The purpose of this community service is to increase the knowledge of mothers of infants and toddlers about balanced nutrition because if the related knowledge is still lacking, then the practice of a balanced nutrition diet for infants and toddlers is not implemented properly which results in the nutritional status of infants and toddlers being less can even be bad. The stages of the method used in this activity are as follows: 1) Increasing cadre knowledge. 2) Increase knowledge of mothers of infants and toddlers. 3) Making media in the form of balanced nutrition games. 4) Simulation of balanced nutritional eating practices for infants and toddlers using a balanced nutrition game. 5) Evaluation of results in the form of an intelligent balanced nutrition mother race. The results of this activity are knowledge of cadres and mothers of infants / toddlers about nutrition before training is lacking but after being given training is sufficient. Training must be carried out on nutrition for mothers and cadres.